High prevalence of focal and multi-focal somatic genetic variants in the human brain - Michael J. Keogh (Nature Portfolio, 2018)
Similar to cancers, somatic mutations might lead to neurodegenerative diseases. Here, the authors perform ultra-deep sequencing of 102 genes in 173 adult human brains, detect somatic mutations in 54 brains, and develop a mathematical model to estimate the frequency of mutated foci in human brains.